Modelling and Analysis of 18-Pulse Rectification System for DC Traction Power Substation - Shukran A.I.M.; Toh C.L.; Tan C.W. (Institute of Electrical and Electronics Engineers Inc., 2023)
DC transformers; Electric rectifiers; Electric substations; IEEE Standards; Reactive power; Rectifying circuits; 18-pulse rectification; Ac and dc; AC filters; Eighteen-pulse diode rectifier; Grid current; Harmonics distortion; Modelling and analysis; Phaseshifting transformer (PST); Pulse diode rectifiers; Traction power sub stations; Harmonic analysis